2015
DOI: 10.1038/nn.4181
|View full text |Cite
|
Sign up to set email alerts
|

Mapping DNA methylation across development, genotype and schizophrenia in the human frontal cortex

Abstract: DNA methylation (DNAm) is important in brain development, and potentially in schizophrenia. We characterized DNAm in prefrontal cortex from 335 non-psychiatric controls across the lifespan and 191 patients with schizophrenia, and identified widespread changes in the transition from prenatal to postnatal life. These DNAm changes manifest in the transcriptome, correlate strongly with a shifting cellular landscape, and overlap regions of genetic risk for schizophrenia. A quarter of published GWAS-suggestive loci … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
458
5
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(504 citation statements)
references
References 62 publications
29
458
5
3
Order By: Relevance
“…There was evidence of heterogeneity in the FCO signature fraction in brain and muscle according to fetal gestational age. This observation, which is consistent with previous studies in fetal brain (Jaffe et al 2016) suggests that the transition observed postnatally in hematopoietic cells occurs prenatally in a tissue dependent fashion. This observation begs the question whether the kinetics of stem cell maturation are unique to each tissue.…”
Section: Cold Springsupporting
confidence: 93%
“…There was evidence of heterogeneity in the FCO signature fraction in brain and muscle according to fetal gestational age. This observation, which is consistent with previous studies in fetal brain (Jaffe et al 2016) suggests that the transition observed postnatally in hematopoietic cells occurs prenatally in a tissue dependent fashion. This observation begs the question whether the kinetics of stem cell maturation are unique to each tissue.…”
Section: Cold Springsupporting
confidence: 93%
“…Differences in latent RNA quality and the underlying cellular composition of homogenate tissue sources (20)(21)(22) are two of the strongest confounding factors in postmortem human studies. The qSVA approach here that uses quality-associated features is analogous to our previously proposed approach that uses celltype-associated features to untangle the confounding effects of cellular composition (sparse PCA) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a vast amount of methylation arrays of postmortem human brains have been released recently [23,24]. These latest advances may implicate the importance of methylation paterns in schizophrenic patients.…”
Section: Epigenetics and Dna Methylation Proiles In Schizophreniamentioning
confidence: 99%